Effect of Some Admixtures on the Surface Properties of the Hydration Products of Silica Fume/Ca(OH) Mixtures - E.E. Hekal; N.A. Mousa (Adsorption Science & Technology)
The effect of sodium naphthalene formaldehyde sulphonate polycondensate and stearic acid on the surface properties of calcium silicate hydrates, formed as a result of the hydration reaction between silica fume and calcium hydroxide, has been examined by the use of low-temperature nitrogen gas adsorption techniques. In addition, the interaction of such admixtures with the calcium silicate hydrates formed was investigated by infrared (IR) spectroscopic analysis. It was observed that both admixtures increased the specific surface area of the calcium silicate hydrates quite considerably relative to the behaviour of a blank sample (i.e. without addition of admixture), especially during the initial stages of hydration (after 24 h). IR examination demonstrated that the admixtures used did not interact chemically with the calcium silicate hydrates although physical interaction was possible.